PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PENGGUNA JASA TRANSPORTASI GOJEK DI JAKARTA - Tulus Caisario Yehezkiel; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2017)
The growth of public transportation in Jakarta is not very significant as many Jakartaresidents prefer to use private vehicles rather than using public transportation, because thecitizens of DKI Jakarta have not found a convenient, safe, and fast public transportation tothe destination. High crime rates in public transport cause consumers to be reluctant to usepublic transport. GoJek, which operates in the ojek transportation service online is relativelymore acceptable to Jakarta citizens as a solution to reach the destination quickly, and alsosafe from crime. In addition, the GoJek service tariff is very rational as it is based on thedistance traveled to the place, but with the increasingly tight competition in thetransportation of motorcycle taxis online, GoJek strives to provide the maximum quality oservice for consumers so that consumers get satisfaction in using GoJek services. Thepurpose of this study is to determine the influence of reliability, responsiveness, assuranceempathy, physical evidence of GoJek consumer satisfaction in Jakarta partially orsimultaneously. The population of this research is the people residing in DKI Jakarta, and have usedthe transportation service of GoJek. The sum of these populations is unknown. The samplesize is calculated with the slovin formula determined as 96 people. Sampling technique usingpurposive sampling. Data tabulated from the results of interviews first tested the validity andreliability, and then further analyzed by regression analysis. The result of this research shows that respondent's category of reliability is reliableresponsive variable category is responsive, assurance variable category is assured, andempathy variable category is Empathy, and it is concluded that partially or simultaneouslythere is positive and significant influence between Reliability , Responsiveness, assuranceempathy, physical proof of Customer Satisfaction of transportation service users in Jakartabesides it can be concluded also that the biggest influence of service quality to customersatisfaction is physical evidence variable having coefficient value 1,680 and followed byreliability variable having Coefficient value 1.223, then followed by other variables Gojek needs to improve customer service by maintaining better communicationtactical service, sprightly, with support for communication networks and mobile phones moreadequate, and the driver should further increase the field coverage area coverage. Inaddition, the appearance of the driver should look more neat, fragrant, not pinched byalways paying attention to the work support facilities for consumers, such as helmetsraincoat, nose cover, etc and ensure it is complete, in good condition, clean, and ready touse.